ACHIEVEMENTS IN THE FIELD OF CREATION SOLAR POWER STATION (analytical review) - Sergeyev, I. Yu.; Protsenko, O. B. (Electronics and Control Systems, 2018)
An overview of publications in the field of creating power plants using solar radiation energy - solar stations is given. It is shown that solar energy is the source of energy of the future, an exceptionally clean, simple and natural way of generating electricity, which is very little associated with biological danger. Solar energy practically does not cause any harm to the environment, is an environmentally friendly source, does not expend mineral resources and does not violate the thermal balance of the planet. In the next decade, solar energy will become commercially viable. In the future, solar energy may become the main source of continuously renewable energy in the Earth’s biosphere.